TOPOGRAPHICAL ANATOMY OF ULNAR NERVE IN THE HAND – A CADAVERIC STUDY - A.PRIYADARSHINI GOUTHAMAN; M.ZAREENA BEGUM; M. YUVARAJ; M. YUVARAJ; M.KUMARESAN; M. YUVARAJ (International Journal of Pharma and Bio Sciences, 2017)
Topographical assessment and evaluation of the nerves play a major role in giving a detailed background of the course and possible variation that the nerve can possess. This study is aimed at assessing the course, distribution, communications of ulnar nerve in the hand. Ulnar nerve is frequently involved in entrapment neuropathy at the region of Guyon’s canal. Therefore, the topographical assessment of ulnar nerve in the hand plays a vital role in diagnosis and management of ulnar nerve entrapment syndrome. The course, distribution and communication patterns of ulnar nerve in the hand was studied in upper extremities of 40 formalin preserved cadavers. Specimens were carefully dissected and ulnar nerve anatomy was studied. A possible anomalous course of ulnar nerve anatomy can lead to a compression syndrome leading to sensori – motor deficit.